Bedside clinical signs associated with impending death in patients with advanced cancer: Preliminary findings of a prospective longitudinal cohort study - Hui, David (Cancer, 2015)
BACKGROUND: We recently reported 5 highly specific physical signs associated with death within 3 days among cancer patients that may aid the diagnosis of impending death. In this study, we examined the frequency and onset of an additional 52 bedside physical signs and their diagnostic performance for impending death. METHODS: We enrolled 357 consecutive patients with advanced cancer admitted to acute palliative care units at two tertiary care cancer centers. We systematically documented 52 physical signs every 12 hours from admission to death or discharge. We examined the frequency and median time of onset of each sign from death backwards, and calculated their likelihood ratios (LRs) associated with death in 3 days. RESULTS: 203/357 (57%) patients died at the end of the admission. We identified 8 physical signs that were highly diagnostic of impending death. These signs occurred in 5-78% of patients in the last 3 days of life, had a late onset, and had a high specificity (>95%) and high positive LR for death within 3 days, including non-reactive pupils (positive LR 16.7, 95% confidence interval 14.9-18.6), decreased response to verbal stimuli (8.3, 7.7-9), decreased response to visual stimuli (6.7, 6.3-7.1), inability to close eyelids (13.6, 11.7-15.5), drooping of nasolabial fold (8.3, 7.7-8.9), hyperextension of neck (7.3, 6.7-8), grunting of vocal cords (11.8, 10.3-13.4), and upper gastrointestinal bleed (10.3, 9.5-11.1). CONCLUSION: We identified 8 highly specific physical signs associated with death within 3 days in cancer patients. These signs may inform the diagnosis of impending death.